The Role of Labor Traditions in the Labor Education of Students (Eurasian Research Bulletin, 2023)
The article provides information that the study of labor traditions is important, laying the foundations for scientifically sound use when choosing a profession. At the same time, information is provided that a number of the following socio-pedagogical qualities are required from the teacher.